Taxonomic novelties in Southern Brazilian Amaryllidaceae – III: Hippeastrum multiflorum, a new species from Rio Grande do Sul - Büneker, Henrique Mallmann; Soares, Kelen Pureza; Assis, Lucas Coelho de; Witeck-Neto, Leopoldo (Balduinia, 2018)
Hippeastrum multiflorum is an endemic saxicolous new species from Rio Grande do Sul, southern Brazil. It is described, illustrated, and data about its geographic distribution and ecology are provided. The new species has morphological affinity with H. sanctaecatharinae and H. ramboi.